Analysis of Dynamic Characteristics for Face Gas Dynamic Seal. (2015) - Falaleev, S.V.; Vinogradov, A.S.
Abstract: Increasing of aircraft gas turbine engines and power plants efficiency is one of important design problems. One of possible ways of this problem solution is decreasing of leakage through the support seals. Some kinds of seals applied in supports of aircraft engines are known. A face gas dynamic seal is one of the most effective. The considerable part of damages in face gas dynamic seals takes place from dangerous vibration in it. A two-mass dynamic model which is the most applicable in practical cases for face gas dynamical seal is considered in a present paper. The theoretical and experimental analysis of dynamic condition of seal is fulfilled. Range of applicability for face gas dynamical seals on amplitude and frequency is defined. It is possible to use the results of present researches for development of new seal structures, and for application of seals at compressors with magnetic supports.